A cartography Amazonian indigenous literature - Espino Relucé, Gonzalo (2022)
This article presents a cartography of the Amazonian indigenous literatures. It addresses the main problematic nuclei of this as an expression that distinguishes and registers a double status: the continuity of the ancient legacy and the recreation and creation of culture in the field of contemporary writing. The first referred to the ancestral condition that is expressed as the validity of the tradition and oral memory of the indigenous peoples and the second referred to the transformations as part of the development of the modernization of Peru. So there are different processes in which the specialist —foreign; priest, anthropologist, linguist— collects and studies the Amazonian cultures of those in which members of the community —an indigenous subject of enunciation— do so as a representation of their ethnic group and in the letter of their language to write their own literature. In this way, it is proposed that the new arrives with the traces of the conquest of the letter by the native peoples, a new literature that will not be a process of inclusion but the progressive appropriation of the technology of writing and the visibility of discursive manifestations native to the ethnic diversity of the Peruvian Amazon. At the same time, he establishes an itinerary that links territory, culture and language and postulates that these expressions are related to the territory as situated poetics. Formally, emphasis is placed on some thematic axes that converge and give shape to the indigenous word: their cosmogony, their humanity —their origins and other people—, their relationship with the spirits, their poems-songs, the Inka Malo and the impact of modernization in which memory of ancestors and historical contexts dialogue.